Odkrivanje spremenljivih izvorov s širokokotnimi pregledi neba - Bricman, Katja (Matrika, 2016)
Astrophysical objects can change their brightness due to different physical processes, and can therefore be detected as variable or new light sources in the sky. Variability differs in both time and brightness from one source to another, however variable sources or transients can be divided into two groups: variable stars and high-energy objects. Sky survey telescopes, which cover the same part of the sky in short time intervals, made the detection of transients an interesting topic in astrophysics. In this article different types of transients are presented, followed by a description of a few notable sky survey telescopes.
Keywords: astronomija; astronomy; gamma-ray bursts; izbruhi sevanja gama; spremenljive zvezde; supernovae; supernove; survey telescopes; širokokotni pregledi neba; variable stars